The Pragmatics of Perception and Cognition in MT Jeremiah 1:1-6:30: A Cognitive Linguistics Approach - Hayes, Elizabeth R. (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft, 2008)
Biographical note: Elizabeth R. Hayes, University of Oxford, Bothell, USA.